Comportamiento del consumidor y nostalgia Revisión y análisis bibliométrico sobre retromarketing - Matías Enrique Membiela-Pollán; Xose Picatoste-Novo; Jo\~ao Paulo de Jesús Faustino (Atlantic Review of Economics (ARoEc), 2021)
– Social and individual awareness of aspects related to sustainability has given rise to the appearance of a new style of consumption that is more conscious and focused on the quality and quality of products beyond quantity. In addition, there is a growing trend towards the demand for goods linked to memories or feelings of rootedness. Academic literature has echoed these trends. Among the published works are those of retro marketing, also called nostalgia marketing. Studies on retromarketing have grown notably in recent years, as has its business use linked to the push-in demand for retro / vintage products. In this sense, the objective of this article is dual since it both proposes an approach to the state of the question and an ad hoc bibliometric analysis. Bibliometrics is enriching because it sheds light on the number of documents, citations, authors, network densities, areas of knowledge, types of publication, and other items. In the present case and from the results obtained in the Scopus and Web of Science databases, retromarketing studies are increasing, mostly located in Business and Management, and a concentration on the number of authors investigating this motive.
Keywords: M21; M30; 330; comportamiento del consumidor; retromarketing; bibliometría; nostalgia; consumer behaviour; retromarketing; bibliometrics